Measuring R&D effectiveness-I Robert Szakonyi offers an approach based on how well an R&D department performs ten key activities - Szakonyi, Robert
How well an R&D department performs ten basic activities indicates its effectiveness-and how it can improve.
A new approach to measuring R&D effectiveness focuses on what R&D managers intuitively know is important. Ten R&D activities, from selecting the projects to linking R&D to business planning, are measured by identifying at which of six levels an R&D department is operating. The six levels are : (1) issue is not recognized; (2) initial efforts are made toward addressing issue; (3) right skills are in place; (4) appropriate methods are used; (5) responsibilities are clarified; and (6) continuous improvement is underway. With this approach, R&D managers can identify which activities their department needs to improve in and how it needs to improve.
Keywords: Effectiveness--R&D.